The physics of rotational tunneling: hole-burning spectroscopy of methyl groups: Molecular Solids - Somoza, Mark M.; Friedrich, Josef (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
Methyl groups are most outstanding quantum systems due to their inherent symmetry properties which cannot be destroyed by any kind of lattice disorder. We show how optical hole-burning techniques can be employed to measure rotational tunneling relaxation processes. Since the tunneling parameters are extremely sensitive to changes in the host lattice, there is a rich variety of relaxation phenomena that can be observed. Hole-burning techniques have the capability of measuring not only extremely slow processes with high precision but also rather fast processes. We exploit this possibility to show that the relaxation times at 2 K change by 14 orders of magnitude if the permutation symmetry of the methyl group is destroyed by asymmetric deuterium substitution.